Mucosal Regulatory T Cells and T Helper 17 Cells in HIV-Associated Immune Activation - Pandiyan, Pushpa; Younes, Souheil-Antoine; Ribeiro, Susan Pereira; Talla, Aarthi; McDonald, David; Bhaskaran, Natarajan; Levine, Alan D.; Weinberg, Aaron; Sekaly, Rafick P. (Frontiers in Immunology, 2016)
Abstract Residual mucosal inflammation along with chronic systemic immune activation is an important feature in individuals infected with human immunodeficiency virus (HIV), and has been linked to a wide range of co-morbidities including malignancy, opportunistic infections, immunopathology and cardiovascular complications. Although combined antiretroviral therapy (cART) can reduce plasma viral loads to undetectable levels, reservoirs of virus persist, and increased mortality is associated with immune dysbiosis in mucosal lymphoid tissues. Immune-based therapies are pursued with the goal of improving CD4+ T-cell restoration, as well as reducing chronic immune activation in cART-treated patients. However, the majority of research on immune activation has been derived from analysis of circulating T cells. How immune cell alterations in mucosal tissues contribute to HIV immune dysregulation and the associated risk of non-infectious chronic complications is less studied. Given the significant differences between mucosal T cells and circulating T cells, and the immediate interactions of mucosal T cells with the microbiome, more attention should be devoted to mucosal immune cells and their contribution to systemic immune activation in HIV infected individuals. Here we will focus on mucosal immune cells with a specific emphasis on CD4+ T lymphocytes such as T helper 17 cells and CD4+Foxp3+ regulatory T cells (Tregs), which play crucial roles in maintaining mucosal barrier integrity and preventing inflammation respectively. We hypothesize that pro-inflammatory milieu in cART treated patients with immune activation significantly contributes to enhanced loss of Th17 cells and increased frequency of dysregulated Tregs in the mucosa, which in turn may exacerbate immune dysfunction in HIV infected patients. We also present initial evidence to support this hypothesis. A better comprehension of how pro-inflammatory milieu impacts these two types of cells in the mucosa will shed light on mucosal immune dysfunction and HIV reservoirs, and lead to novel ways to restore immune functions in HIV+ patients.